Analisis faktor yang mempengaruhi permintaan kredit pemilikan rumah (KPR) di Kota Palembang: Kasus nasabah KPR Bank BTN - Deri Sandria; Nazeli Adnan; Saadah Yuliana (Jurnal Ekonomi Pembangunan, 2016)
The purpose of the study was to investigate the effect of income, house prices and interest rates on the demand for housing loans (KPR) at BTN Bank in Palembang city. This study uses secondary data and primary data. The method used is a quantitative approach by applying a linear regression model. The findings from the results of the study indicate that variations in income variables, house prices and interest rates explain the variable demand for mortgages by 57.6%. In addition, another finding from this study is that the income variable has an insignificant influence on the demand for mortgages, while the variable house prices and interest rates have a positive and significant influence on the demand for mortgage loans in Palembang city.